Perspectives of racially minoritized youth with disabilities on addressing ableism and other forms of discrimination - Sally Lindsay; Janice Phonepraseuth; Van Slothouber; Jaden Lo; Jennifer N. Stinson; Sharon Smile (PLoS ONE, 2025)
Background Racially minoritized youth with disabilities often encounter more extensive forms of discrimination. However, little is known about youth perspectives for addressing disability-related and other forms of discrimination, which is important for enhancing the participation and inclusion of youth with disabilities. This study explored the recommendations of youth with disabilities for addressing barriers and multiple forms of discrimination. Methods This study involved in-depth interviews with a purposive sample of 20 youth with disabilities. We applied an inductive thematic analysis to the transcripts. Results Our findings highlighted the following key themes: (1) addressing barriers in healthcare, education, employment and the legal system; (2) community, social supports and resources; (3) advocacy; and (4) inclusive policies and youth involvement. Conclusions There is a critical need for more inclusive services and support for youth with disabilities, especially those with multiple minoritized identities, to foster safe environments and quality of life.